In-vitro antimicrobial activities of methanol extracts of (2010)
The antimicrobial activities of two Nigerian medicinal plant commonly used as chewing sticks Zanthoxylum xanthoxyloides and Pseudocedrela kotschyi antimicrobial activities were investigated against 7clinical strains of Streptococcus mutans, Staphylococcus aureus ATCC 29213, Candida albicans, Candida tropicalis and Candida krusei ATCC 6825. The antibacterial and antifungal activities of the extracts were determined using the agar well diffusion and surface plate method respectively. Zanthoxylum xanthoxyloides, was active against all the isolates especially on the bacteria with a MIC and MBC of 12.5mg/mL and 25mg/mL respectively. Pseudocedrela kotschyi showed no activity on all the tested isolates except on C. krusei ATCC 6825 with a MIC of 6.25mg/mL. . Streptococcus mutans, S. aureus ATCC 29213 and C. albicans were completely killed within the time period of4hrsbyZ. xanthoxyloides extracts in time kill study. A good correlation was foundbetween the killing curves and the MIC of Z. xanthoxyloides against the tested isolates. Phytochemical screening revealed the presence of alkaloids, tannins, flavonoids, saponins and traces of terpenoids. Ability of Z. xanthoxyloides crude extracts to inhibit the growth of the bacteria and fungi used in this study is an indication that the plant can be used as a source foranti microbial agent in the development and formulation of toothpaste, thus justifying the use of the plant in locally as chewing sticks..